Functional capacity and gender-related differences in Fabry disease. (14th October 2021) - Guglielmi, G; Mollo, A; Bandera, F; Camporeale, A; Frigelli, M; Alfonzetti, E; Lombardi, M; Pieroni, M; Pieruzzi, F; Guazzi, M
Abstract: Background: Fabry disease (FD) is a rare x-linked lysosomal storage disease characterized by accumulation of glicosphingolipids in several organs, including the heart. Cardiac involvement manifests as left ventricular (LV) hypertrophy, often complicated by myocardial fibrosis. The impact of disease on functional capacity is not well defined, as well as the potential gender-related differences. Aim: To evaluate the functional capacity in a cohort of FD patients with different degree of cardiac involvement. Methods: Seventy-two patients were prospectively enrolled from March 2015 to December 2019. Patients underwent cardiac magnetic resonance (CMR) and cardiopulmonary exercise test (CPET) with cycle ergometer. In addition to standard CPET parameters, Chronotropic Index (CI) was calculated as (HR max − HR rest) / (HR max predicted − HR rest), adjusting with HR max predicted calculated as 119 + (HR rest/2) − (age/2) in case of beta-blockers treatment. Results: CMR showed left ventricle (LV) hypertrophy (LV mass greater than normal reference value) in 36.1% of patients, LGE and reduced T1 values were detected in 30.6% and 59.7% of subjects respectively. Twenty-eight patients were males (39%), the median age was 40 (28–54) [median (25th–75th)] years and only 11 (15%) subjects were on beta-blockers. All subjects performed a maximal test [RQ max = 1.21 (1.14–1.26)] using a ramp protocol of 15 (15–20) Watt. The absolute peakVO2 was 18.2 (15.75–24.08) mL/min/kg, whilst the percentage of predicted peakVO2 was 67.7 (57.3–76.6)%. The chronotropic response of the overall population was characterized by reduced peak heart rate (HRmax) [80.3 (73.8–87.6)% of predicted], and diminished chronotropic index (CI) [0.67 (0.55–0.77) normal value: 0.80], but preserved heart rate reserve (HRR) [21 (12–28) bpm]. Ventilatory efficiency was preserved [VE/VCO2 = 25.70 (23.18–28.00)]. At gender analysis, men showed higher absolute peakVO2 [men vs females: 19.95 (17.20–28.28) vs 17.80 (15.50–21.28) mL/min/kg, p=0.02] but lower percentage of predicted [64.24 (52.58–70.61) vs 70.75 (59.05–78.02)%, p<0.001] than females. No differences between genders were observed in chronotropic response [HRmax = 138 (108–154) vs 142 (135–153) bpm, p=0.38; HRR = 22 (13–36) vs 20 (11–26), p=0.097; CI: 0.67 (0.51–0.76) vs 0.67 (0.58–0.79), p=0.33], whilst females showed a lower peak O2 pulse (VO2/HR) than males [men vs females: 12.08 (10.04–13.64) vs 7.76 (6.88–9.22), p<0.001], possibly related to gender differences in LV dimensions and stroke volume. Conclusions: This large cohort of FD patients with different degree of cardiac involvement showed a significantly impaired functional capacity, mainly characterized by relevant chronotropic incompetence (independent from the use of beta-blockers), consistent with systemic autonomic dysfunction. The degree of chronotropic incompetence was similar between the genders, but females showed higher predicted peakVO2 despite a lower peak O2 pulse. FUNDunding Acknowledgement: Type of funding sources: None.